The Legend of Biton and Faaro: A Reinterpretation of a Creation Myth from the Epic of Bamana Segu Performed with Puppets and Masks in Mali (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
This contribution calls attention to Malian masquerades that reinterpret narrative material drawn from the epic of Bamana Segu through puppets and masks. After providing a general overview of African puppetry, the essay zooms in specifically on the Malian village of Kirango, located on the bank of the Niger River about 35 kilometers northeast of the city of Ségou. The inhabitants of this village (Bamana farmers and Bozo fishermen) celebrate masquerades in which puppets and masks are made to dance by puppeteers whose performance is accompanied by drum-mers and singers. In this context, no difference is made between puppets and masks: both are called sogo (‘animal’), because many of them represent animals such as the hippopotamus, the crocodile, various types of fish (Bozo), antelopes and the buffalo (Bamana). The essay then introduces two characters from the epic of Bamana Segu, Faaro (water spirit and creator god) and Biton (Mamari Coulibaly, a historical Bamana king who, according to a widespread legend, acquired power with the help of Faaro); and it goes on to discuss Faaro’s role in Bozo and Bamana masquerades and explain how a 2009 Bozo performance recreated the legend of Faaro and Biton. The final sections of the essay reflect on the masquerades’ significance with respect to collective memory and cultural identity as well as their possible evolution in the future.
Keywords: Mali; Kirango; Bozo; Bamana; masquerades; puppets; masks; epic of Bamana Segu; Biton; Faaro